A Juridical Analysis of Constitutional Court Decision No. 30/PHPU.BUP-XXIII/2025 on the 2025 Magetan Regency Local Election Results Dispute - Naufal Ma’ruf Fadhlurohman; Sarjiyati; Taufiq Yuli Purnama (Faculty of Law, University of Dr. Soetomo, 2026)
This study analyzes Constitutional Court Decision Number 30/PHPU.BUP-XXIII/2025 concerning the dispute over the 2025 Magetan Regent Election results. It aims to examine the judges’ legal reasoning and its implications for electoral justice. Using a normative juridical method with a case- and literature-based approach, the study finds that the Court applied a substantive justice approach by assessing structured, systematic, and massive (TSM) violations and ordering re-voting at four polling stations. This decision directly affected vote distribution among candidates and reinforced the Court’s role in safeguarding democracy. However, challenges such as inconsistencies in handling electoral violations and structural issues like political costs and nepotism remain. In conclusion, the decision strengthens electoral law enforcement while highlighting the need for improved supervision and systemic reform to ensure fair and credible local elections.